Murcha de fusário em cafeeiro conilon: dinâmica espaço-temporal - Belan, Leonardo Leoni (2022)
Brazil is a reference in technologies, quality, production and coffee exports to the whole 30 world, and the State of Espírito Santo is a reference in productivity, techniques and 31 technologies for the management of conilon coffee in our country. However, many 32 diseases interfere with the productivity and management of crops, reducing their useful 33 life, among these, the recent fusarium wilt in Conilon coffee trees reported in the country 34 is spreading and little is known about it in our territory, due to the diversity of existing crops. 35 To resolve doubts related to the new pathosystem, epidemiological studies were carried 36 out in four crops of Coffea canephora, chosen for similarity of management and incidence 37 of symptomatic plants to the disease, being two crops of clonal propagation, containing the 38 cultivar conilon Vitória – 'Incaper 8142' and two crops of seminiferous propagation of the 39 cultivar Robusta Tropical - EMCAPER 8151 in the south of Espírito Santo state. They were 40 evaluated monthly, during three seasons, regarding the incidence and location of 41 symptomatic plants, identifying the evolution of the disease in time and space. To classify 42 the temporal pattern, fusarium wilt progress curves were plotted on Conilon coffee using 43 their incidence and adjustment values in monomolecular, logistic, exponential and 44 Gompertz epidemiological models. To classify the spatial pattern of the disease, the 45 dynamics and structure of foci, ordinary sequences of Runs and Doublet, were analyzed. 46 With the analysis, it was found that there was an epidemic in all areas evaluated, 47 regardless of whether it was clonal or seminiferous, which were adjusted to the 48 monomolecular model, and the pattern of distribution and compaction of foci varied 49 between areas and for clones, giving a view of the resistance between them and the 50 distribution in the planting line was in aggregates for some clones.